Factors associated with mortality and long-term outcomes of pediatric acute kidney injury in a resource limited setting (2023)
Introduction: Despite being a leading cause of morbidity and mortality globally, acute kidney injury (AKI) is worse in resource-limited areas. This study explores AKI incidence, in-hospital mortality, and long-term outcomes in resource limited settings. Methods: This was a prospective study of children with AKI from2014 to 2019. KDIGO 2012 defined AKI. We assessed the etiology, in-hospital mortality, and long-term outcome of AKI in a mission hospital. Results: Only 169 of 201 AKI patients had complete data. The ages ranged from 1.08 months to 17.5 years; 65.7% were male and 65.1% were from lower socioeconomic class. The incidence of AKI was 59.6 cases per 1,000 persons (95%CI: 5.42, 47.1). Most patients had stage 1 KDIGO AKI (91; 53.8%). 1–5 years old had the highest incidence of AKI (65; 38.5%); sepsis (26.6%), severe malaria (15.4%), and nephrotic syndrome (14.8%) were common AKI causes. Fever (72.8%), pallor (52.1%), and vomiting (45.6%) were the most common symptoms. Thirty two (27.8%) patients had high blood pressure. In-hospital mortality was 14.8% (95% CI: 9.8, 21.1). The cumulative incidence of AKI-related mortality was 93.2 per 1,000 person years. Poor outcome was associated with breathlessness, hyponatremia, and leukocytosis. Kaplan-Meier survival curve showed 81% (CI: 74–87%) survival after 5 years of AKI. On Cox proportional-hazards analysis, the absence of breathlessness (HR: 2.537, 95%: CI 1.210–5.317) and hyponatremia (HR: 2.914, 95% CI: 1.343–6.324) were associated with increased survival. Conclusion: In resource-limited settings, infectious diseases and nephrotic syndrome are common causes of AKI. Factors associated with mortality include breathlessness and hyponatremia